A Case Study Of A Malaysian Accounting Software Company UBS Corporation Berhad - Han, Edward Chung Kit (2003)
This project is intended to study comprehensively and thus explore the case of UBS Corporation Berhad. As a main objective, the research provides the opportunity to act as a consultant or decision maker in handling the issue of an organization.